Looking to Autoethnography as Spiritual Practice - Bilgen, Wendy Anne (Religions, 2022)
In this autoethnographic account, I explore through creative analytic practice (CAP) how autoethnography has become a practice for spiritual connection. Inspired by Martin Buber’s I-Thou philosophy, I discuss how autoethnographic encounters have the potential to emulate what is characterized by Buber as encounters with an Eternal Thou. In Buber’s conceptualization, when an individual I encounters a Thou, in a dialogical relationship of mutual honor and embrace of shared humanity, an Eternal Thou encounter is experienced. The qualities of the I-Thou encounter are mirrored in autoethnography as the autoethnographer (I) and the reader/participant (Thou) share a numinous, sacred, spiritual exchange. Processes inherent to autoethnographic work enable the conditions wherein the sacredness of I-Thou encounters are nourished. I invite the reader to wonder with me about the ways that authentic, vulnerable, and critical engagement with one’s own story paves the way for I-Thou experiences to be ignited and imaginative possibilities multiplied so that individual and social transformation might follow. Finally, I question whether autoethnography might help fill a gap in our current spiritual research paradigms.